Pengaruh Pemahaman Perpajakan Dan Kemauan Membayar Pajak Terhadap Kepatuhan Wajib Pajak UMKM - Luturmas, Heniditi; Simbolon, Remista; Karundeng, Meidy L (Maisyatuna, 2024)
The objective about research is to identify that impact in understanding know more deeply about a topic or phenomenon being researched, namely taxation and willingness to pay taxes on taxpayer compliance (MSMEs). Through a qualitative approach, by filling out a questionnaire filled in by 48 respondents, by analyzing statistics, namely, classical assumptions analysis, multiple linear analysis, significance evaluating, and analysis of correlation coefficients and determination. Both partially and simultaneously, apart from that, this test shows that the independent test variables have a significant influence on MSME taxpayer compliance with a total significance of 0.00 or less or lower than 0.05.